Exploring Socio-Cultural Network, Open Innovation, and Entrepreneurial Orientation: A Theoretical Integration (Journal of Governance and Development (JGD), 2019)
The socio-cultural network has provided an important theoretical contribution toward the understanding of the concept of actors and cultural elements to be nodes together, and consequently affect the entrepreneurial activity. However, the socio-cultural network theory seems to be less concern and remain understudied in the respect of the innovation perspectives. Therefore, the aim of this paper is to integrate, from a theoretical perspective, the socio-cultural network and open innovation altogether for explaining the entrepreneurial orientation. In this sense, this paper points out that the open innovation approach could be apt in the socio-cultural network framework to develop future research in analysing the decisions of entrepreneurial orientation.